ANALISIS FAKTOR DETERMINAN DEMOGRAFI DENGAN KEJADIAN TUBERCULOSIS MULTIDRUG RESISTANT TUBERCULOSIS (MDR-TB) - Soesanti Soesanti; Abd Hakim Husen (NHM PRESS, 2022)
Tuberculosis (TB) is one of the top 10 causes of death worldwide. Multidrug Resistant Tuberculosis (MDR-TB) is TB that is drug resistant to at least 2 (two) most potent anti-TB drugs. This study aims to determine the relationship between age and sex factors with the incidence of Multidrug Resistant Tuberculosis (MDR-TB). This cross-sectional study involved 37 people with pulmonary tuberculosis in the 2019-2021 period which was carried out in the work area of ​​the Ternate City Health Office. Data analysis using chi square test. The results showed that the characteristics of MDR-TB patients in Ternate City were 24 respondents (64.9%) male and 13 female respondents (35.1%). Most of the patients aged 35-44 years were 14 respondents (37.8%), while those aged 15-34 and 45->60 years were on average only 4 and 5 respondents. The incidence of tuberculosis multidrug resistant tuberculosis (MDR-TB) is influenced by age > 35 - 44 years, while the type of chlamydia is not related.